1997
DOI: 10.1016/s0029-7844(96)00509-1
|View full text |Cite
|
Sign up to set email alerts
|

The missing link in rhesus monkey amniotic fluid volume regulation: Intramembranous absorption

Abstract: These results suggest that intramembranous absorption occurs and may play an important role in rhesus AF volume regulation and composition. Furthermore, this animal model, which closely resembles the human, may provide valuable insight into abnormalities of human AF volume regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 14 publications
0
90
1
1
Order By: Relevance
“…Alternatively, contrast medium from the maternal circulation may equilibrate directly into the amniotic fluid by passive intramembranous diffusion and this fluid is then also swallowed by the fetus [9].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, contrast medium from the maternal circulation may equilibrate directly into the amniotic fluid by passive intramembranous diffusion and this fluid is then also swallowed by the fetus [9].…”
Section: Discussionmentioning
confidence: 99%
“…Following keratinization of the fetal skin (slightly after mid-gestation), amniotic fluid is considered to be a product mainly of fetal urination which approximates 30% of fetal body weight daily, and at term ranges between 600 and 1200 mL/day [1][2][3] .…”
Section: Physiological Dynamics Of Amniotic Fluidmentioning
confidence: 99%
“…Similarly, in animal studies in which fetal swallowing was prevented, fetal urine output remained normal and amniotic fluid volume was not different from that of the controls after 2 -3 weeks 2 . Gilbert and Brace 3 demonstrated that absorption through the intramembranous pathway was increased with ligation of the fetal esophagus. Regarding amniotic fluid turnover, late in gestation when amniotic fluid volume averages 700 -800 mL, 1000 mL fluid flows into and out of the amniotic compartment daily 1,2 .…”
Section: Physiological Dynamics Of Amniotic Fluidmentioning
confidence: 99%
“…By term, the amount of amniotic fluid swallowed by the fetus is between 500 and 1,000 mL/day. 29 The second route for reabsorption into the fetal circulation is the intermembranous pathway. This pathway involves the absorption of amniotic fluid across the amnion and into the fetal vasculature driven by osmotic differences.…”
mentioning
confidence: 99%
“…This pathway involves the absorption of amniotic fluid across the amnion and into the fetal vasculature driven by osmotic differences. 29 In the last two trimesters of pregnancy, fetal exposure to ethanol is further prolonged. This is the result of the recurrent cycle of fetal swallowing of the amniotic fluid containing ethanol, and elimination of urine containing alcohol back into the amniotic fluid.…”
mentioning
confidence: 99%